2020
DOI: 10.1039/d0ta08123j
|View full text |Cite
|
Sign up to set email alerts
|

Iron-regulated NiPS for enhanced oxygen evolution efficiency

Abstract: Development of robust and highly active electrocatalysts for oxygen evolution reaction (OER) is of significance for next-generation renewable energy storage and conversion. Herein, for the first time, we report pyrite-type...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 65 publications
3
20
0
Order By: Relevance
“…XPS was further used to investigate the surface chemistry after the OER and HER stability tests at a current density of 500 mA cm -2 for 10 h. XPS inspection revealed that after extended OER at a high current density, signals from both S and P were significantly diminished (Figure S13, Supporting Information), suggesting that NiFeSP was oxidized into Fe-/Ni-oxyhydroxide under anodic OER conditions. [24,40] No MS and MP bonding could be detected anymore in all highresolution XPS spectra, and there was only a weak peak centered at 132.8 eV in P2p XPS spectrum that can be attributed to PO 4 3species (Figure S13e, Supporting Information). This indicates that substantial compositional change occurred during the OER, consistent with previous reports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…XPS was further used to investigate the surface chemistry after the OER and HER stability tests at a current density of 500 mA cm -2 for 10 h. XPS inspection revealed that after extended OER at a high current density, signals from both S and P were significantly diminished (Figure S13, Supporting Information), suggesting that NiFeSP was oxidized into Fe-/Ni-oxyhydroxide under anodic OER conditions. [24,40] No MS and MP bonding could be detected anymore in all highresolution XPS spectra, and there was only a weak peak centered at 132.8 eV in P2p XPS spectrum that can be attributed to PO 4 3species (Figure S13e, Supporting Information). This indicates that substantial compositional change occurred during the OER, consistent with previous reports.…”
Section: Resultsmentioning
confidence: 99%
“…First, multi-component electrocatalysts comprising more than one metal (e.g., Fe, Co, and Ni) and/or non-metal (e.g., S and P) species have been demonstrated to show better performance than monometallic phosphide and sulfide, [13b] because the coexistence of multiple elements allows for the exposure of more catalytically active sites, and more importantly the tuning of catalyst's electronic structure that enables to enhance the intrinsic catalytic activity. [14] To this end, bimetallic phosphide/sulfide (Ni x Fe 1-x P/S, [15] (Co 1-x Fe x ) 2 P, [16] NiCoP, [17] and Fe-NiS 2 [18] ), metal phosphosulfide (CoPS, [19] P-NiS 2 , [20] CoS|P/CNT, [21] and FePS 3 [22] ), and multi-metal phosphosulfide (Fe 0.2 Ni 0.8 -P 0.5 S 0.5 , [23] Ni 1-x Fe x PS, [24] P-CoNi 2 S 4 , [12a] and FeCoNiP x S y [25] ), were reported already and exhibited improved electrocatalytic performance thanks to the synergetic interplay of different elements. Second, structure engineering turns out to be an effective strategy for achieving high catalytic performance.…”
Section: Research Articlementioning
confidence: 99%
“…However, the electrochemical performance of the as-prepared FeS 2 /NiS 2 composites was still excellent, which indicates that the combination of metal suldes and surface oxidation to form oxides/ hydroxides can expose more active sites and effectively improve the catalytic activity of the material. 85 In order to verify the practical value of the FeS 2 /NiS 2 HDSNRs catalyst, it was dropped on the gas diffusion layer and used as an air electrode to assemble a self-made zinc-air battery (the composition structure is shown in Fig. 5 86 In particular, it exhibits a peak power density of 130 mW cm À2 at 340 mA cm À2 , which is much higher than that of the Pt + Ir/C catalyst (98 mW cm À2 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the electrochemical performance of the as-prepared FeS 2 /NiS 2 composites was still excellent, which indicates that the combination of metal sulfides and surface oxidation to form oxides/hydroxides can expose more active sites and effectively improve the catalytic activity of the material. 85…”
Section: Resultsmentioning
confidence: 99%
“…In our studies, the SnPS 3 /C anode shows a lower internal resistance and a better rate performance compared to NiPS 3 /C, due to a more uniform carbon distribution. In addition, many synthetic pathways such as the chemical vapor transport method, hydrothermal method, chemical exfoliation method, high pressure method, and so forth were utilized to synthesize the abovementioned double-anion TMPC energy nanomaterials, while these synthesis routes have shown some shortcomings, for example, harsh reaction conditions, lack of phase purity, or difficulty in tuning the atomic ratio of the final sample. ,, Herein, MTPs/C composites were successfully grown in an evacuated quartz tube via a simple high-temperature reaction (see Scheme ). This kind of confined reaction system utilized here plays a crucial role in the formation of a MTPs/C sample due to a strong inhibition effect on the loss of volatile P and S elements.…”
Section: Introductionmentioning
confidence: 99%